2017
DOI: 10.5812/jhealthscope.15167
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Healthy Eating Promotion among Adults with Cardiovascular Metabolic Risk Factors: An Application of Intervention Mapping Framework

Abstract: Background: Intervention mapping (IM) is a systematic development of interventions for designing health promotion programs. Objectives: Promoting physical activity (PA) as well as healthy eating (HE) has an important role in improving individuals with cardiovascular metabolic risk factors (CVMRFs). This paper describes development of an intervention based on intervention mappings' steps to promote PA and HE among Iranian adults with CVMRFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…We have found that methods such as knowledge promotion, modeling, advocacy, regulation, and policy are good ways to promote PA in the workplace. In other studies aimed at promoting PA, techniques, and methods such as goal setting, verbal persuasion and practice with feedback (14,15), modeling (14,15,34), reinforcement, public commitment, and self-monitoring (14) use of images (34), creating new social media links, feedback, information matching, social network mobilization and empowerment (15) facilitation (15,35), environmental marketing and awareness-raising (34), benefits and barriers, social support, problem-solving (36) were used. It is important to pay attention to the existing parameters for the effectiveness of the methods and turn them into practical applications because without considering such conditions, their effectiveness will be affected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that methods such as knowledge promotion, modeling, advocacy, regulation, and policy are good ways to promote PA in the workplace. In other studies aimed at promoting PA, techniques, and methods such as goal setting, verbal persuasion and practice with feedback (14,15), modeling (14,15,34), reinforcement, public commitment, and self-monitoring (14) use of images (34), creating new social media links, feedback, information matching, social network mobilization and empowerment (15) facilitation (15,35), environmental marketing and awareness-raising (34), benefits and barriers, social support, problem-solving (36) were used. It is important to pay attention to the existing parameters for the effectiveness of the methods and turn them into practical applications because without considering such conditions, their effectiveness will be affected.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the literature review showed that factors such as knowledge (4,14,15), PA literacy (16), motivation to follow (14,17), behavioral consequences (14,18), positive attitude towards PA (14)(15)(16)18), behavioral skills (19), perceived sensitivity and intensity (14,15,18), perceived benefits (14,20,21,22), self-efficacy (14,15,18,20,22), social support (4,14,15,18,23), social norms (15,17), structural factors and enabling factors (14,24,25), policies and laws (14,21) environmental factors (the provision of facilities and resources) (15,16,19,24) and organizational support (20,25,26) are effective factors of PA in the workplace.…”
Section: Step 1: Needs Assessmentmentioning
confidence: 99%
“…[ 33 ] In a study by Sabzmakan et al ., also attitude, efficacy, and subjective norms related to healthy food consumption changed significantly after the intervention. [ 34 ] In a study by Hamilton et al . who examined the intervention effect on promoting physical activity and healthy nutrition among the elderly in 2010, subjective norms of physical activity in the intervention group increased significantly after the intervention compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the known benefits of PA worldwide, 31% of adults are physically inactive (8,9). According to the third national surveillance on the NCDs risk factors, about 55% of Iranian adults are less physically active than those recommended by the World Health Organization (WHO) (10).…”
Section: Introductionmentioning
confidence: 99%